FICO Eataly World: the food chain between nature and culture - Accurso Tagano , Lorena (E|C, 2020)
In this article we want to investigate how F.I.C.O, the first agri-food park in the world, organizes information on the Italian food and wine culture for the general public. The guiding research question of this paper is: through the park, what values and aspects of our culinary identity emerge from the story of the park? To answer this question, we will try to understand how the food production chain is organized through the analysis of the spaces that represent the various phases in the park.